2006
DOI: 10.1007/s00335-005-0038-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of a new set of recombinant inbred lines (LGXSM) formed from the intercross of SM/J and LG/J inbred mouse strains

Abstract: A new set of LGXSM recombinant inbred (RI) strains is presented. The RI strain panel consists of 18 remaining strains of the original 55 founding strains. Strain characterization is based on 506 polymorphic microsatellites and 4,289 single nucleotide polymorphisms (SNPs) distributed across the genome. Average microsatellite inter-marker distance is 4.80+/-4.84 Mb or 2.91+/-3.21 F(2) cM. SNPs are more densely spaced at 0.57+/-1.27 Mb. Ninety-five percent of all microsatellite inter-marker intervals are separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 57 publications
1
64
0
Order By: Relevance
“…Because there is more power to detect postnatal compared to prenatal maternal effects (Table S3), the finding of more prenatal maternal effects than postnatal effects cannot be attributed to a simple difference in power and is in direct opposition to the difference in power. Although it may appear surprising that prenatal effects are more persistent than postnatal effects, these results are consistent with those reported by Jarvis et al (2005) for adult obesity and diabetes-related traits in the LGXSM recombinant inbred strains (Hrbek et al 2006).…”
Section: Discussionsupporting
confidence: 88%
“…Because there is more power to detect postnatal compared to prenatal maternal effects (Table S3), the finding of more prenatal maternal effects than postnatal effects cannot be attributed to a simple difference in power and is in direct opposition to the difference in power. Although it may appear surprising that prenatal effects are more persistent than postnatal effects, these results are consistent with those reported by Jarvis et al (2005) for adult obesity and diabetes-related traits in the LGXSM recombinant inbred strains (Hrbek et al 2006).…”
Section: Discussionsupporting
confidence: 88%
“…The SM/J strain is maintained by forced heterozygosity at the agouti locus on mouse chromosome 2. Attempts to fix the strain for either the nonagouti (a) allele or the whitebellied agouti allele (A w ) have ended in strain failure (Hrbek et al, 2006).…”
Section: Materials and Methods Samplesmentioning
confidence: 99%
“…In our laboratory, adult LG/J animals are 16 to 20 g heavier than SM/J animals. The strains show genetic variation for body weight, growth, skeletal morphology, obesity, glucose and insulin levels, and response to a high-fat diet (49 -51) among other features (52). QTL mapping studies of phenotypes used in this study have found that genetic variation is attributable to many loci (6, 7, 11-14, 33, 38, 39, 53) (R.H., J.M.C., C.R., and J.B.W., unpublished work) of relatively small effect (a Ͻ 0.3 SD) with variable dominance, epistatic interactions, and modular pleiotropic gene effects (54).…”
Section: Methodsmentioning
confidence: 99%
“…These SNP markers (see SI Table 4) were chosen from the 4,200 polymorphic markers scored as part of the CTC/Oxford genotyping consortium (www.well.ox.ac.uk/mouse/INBREDS/; ref. 52), which resulted in markers being placed every 4 -5 cM along the genome except in regions that seem to be nonpolymorphic between LG/J and SM/J (52). Genotypes were obtained for all F 2 animals and their F3 offspring.…”
Section: Methodsmentioning
confidence: 99%